Evidence update on the cancer risk of vaping e-cigarettes: A systematic review - Anasua Kundu; Kyran Sachdeva; Anna Feore; Sherald Sanchez; Megan Sutton; Siddharth Seth; Robert Schwartz; Michael Chaiton (Tobacco Induced Diseases, 2025)
Introduction There is substantial interest in the association of vaping e-cigarettes with the risk of cancer. We analyzed this risk in different populations by updating the Kings College London (KCL) review to include the period between July 2021 and December 2023.